Transovarial transmission of Rickettsia spp., Francisella-like endosymbionts, and Spiroplasma spp. in Dermacentor reticulatus ticks - Anna Kloc; Angelina Wójcik-Fatla; Piotr Paprzycki; Lech Panasiuk (Ticks and Tick-Borne Diseases)
Research on the transovarial transmission of pathogens whose reservoirs and vectors are ticks has led to an understanding of the mechanisms related to the circulation and persistence of selected microorganisms in natural foci. The primary aim of this study was to investigate the possibility of transovarial transmission of Rickettsia spp. in Dermacentor reticulatus ticks, and the influence of Francisella-like endosymbionts (FLEs) and Spiroplasma spp. on the efficiency of the egg-laying process and transmission of selected pathogens.In total, 16,600 eggs were obtained under laboratory conditions from 55 females, with an average of 346 eggs per female. Adults, eggs, and hatched larvae were tested using polymerase chain reaction (PCR) for the presence of Rickettsia and endosymbionts.DNA fragments of Rickettsia spp. were found in females (56.4 %) and in pools of eggs (72.9 %) and larvae (62.4 %). FLEs and Spiroplasma endosymbionts were confirmed in females (80 % and 14.5 %, respectively), pools of eggs (81.6 % and 26.1 %, respectively), and larvae (82.7 % and 46.2 %, respectively). Transovarial transmission was confirmed in Rickettsia raoultii, FLEs, and Spiroplasma ixodetis. No correlation was observed between the occurrence of individual endosymbionts and the efficiency of egg laying and transovarial transmission in Rickettsia spp.In conclusion, transovarial transmission of Rickettsia spp., FLEs and Spiroplasma spp. in D. reticulatus plays an important role in their persistence and circulation in the environment. However, further research is required on this topic.